An halisaurine (Squamata: Mosasauridae) from the Late Cretaceous of Patagonia, with a preserved tympanic disc: Insights into the mosasaur middle ear - Fernández, Marta S. (2015)
Fil: Fernández, Marta S. Universidad Nacional de La Plata. Museo de La Plata. División Paleontología de Vertebrados. Buenos Aires, Argentina.